Epibrassinolide and melatonin co-treatment enhances salt tolerance in tomato plants by coordinating photosynthetic efficiency, proline accumulation, and antioxidant defense - Yusuf, Mohammad; Khan, Tanveer Alam; Saeed, Taiba (Frontiers in Plant Science, 2025)
Melatonin (ML) and 24-epibrassinolide (EBL) are both known to help plants cope with abiotic stress. However, their interactive effects on the physiological performance of plants under high salinity have not been fully explored. To address this gap, the present study was conducted to investigate the combined role of ML and EBL in enhancing salt stress tolerance in tomato plants. The effects of ML and EBL, applied individually and in combination, were assessed under high salinity conditions by measuring plant growth, photosynthetic efficiency, stress-related biomarkers, proline metabolism, and antioxidant enzyme activity. The results showed that applying ML before stress and EBL after stress significantly reduced the accumulation of ROS. This effect was achieved by boosting antioxidant activity and regulating key enzymes involved in proline metabolism. These biochemical adjustments, such as enhanced antioxidants and altered proline metabolism, led to reduced lipid peroxidation, lower hydrogen peroxide (H2O2) levels, and decreased electrolyte leakage. Furthermore, the interactive treatment improved photosynthetic efficiency and growth by enhancing the activity of RuBisCO, a key enzyme in carbon fixation. Overall, this study provides novel insights into the synergistic role of EBL and ML in conferring salt stress tolerance through improved proline metabolism, redox regulation, and photosynthetic performance. The findings suggest that the co-application of ML and EBL holds significant potential as an eco-friendly strategy to enhance salinity tolerance in tomato plants, thereby contributing to sustainable agricultural practices under saline conditions.